Pandemic Covid 19: Academic Culture, Lecturer Ability, And Lecturer Performance - Noor, Asmirin; Kustiningsih, Nanik; Intaniman, Sutanto; Leki, Rofinus (Archives of Business Research, 2022)
This research is entitled Pandemic Covid 19; Academic Culture, Lecturer Ability, Lecturer Performance. This study aims to determine the effect of the Covid 19 pandemic on changes in Academic Culture and Lecturer Ability and its impact on Lecturer Performance. This research was conducted on permanent lecturers at STIE Mahardhika Surabaya, STIE Pancasetia Banjarmasin and STIE Cendekia Karya Utama Semarang. Members of the population of this study amounted to 296 people. The sample using the Slovin formula is 74 people. This approach uses a quantitative approach with path analysis tools. Based on the analysis, it was found that the Covid 19 Pandemic had a significant effect on changes in Academic Culture and Lecturer Competence but had an insignificant impact on Lecturer Performance. Meanwhile, Academic Culture and Lecturer Competence also affect Lecturer Performance.